Characteristics of Germline Non-BRCA Mutation Status of High-Risk Breast Cancer Patients in China and Correlation with High-Risk Factors and Multigene Testing Suggestions - Su, Yifan; Yao, Qianlan; Xu, Yuyin; Yu, Chengli; Zhang, Jing; Wang, Qian; Li, Jiwei; Shi, Di; Yu, Baohua; Zeng, Yupeng; Zhu, Xiaoli; Bai, Qianming; et al. (Frontiers in Genetics, 2021)
Background: Expert consensus on BRCA1/2 genetic testing and clinical application in Chinese breast cancer patients recommends that BRCA1/2 testing should be performed in those with clinical risk factors, such as an early onset, triple-negative breast cancer or family history of cancer. With the increasing application of multigene panels, testing for genes beyond BRCA1/2 has become more prevalent. However, the non-BRCA mutation status of Chinese high-risk breast cancer patients has not been fully explored. Methods: A total of 230 high-risk breast cancer patients from Fudan University Shanghai Cancer Center who had undergone peripheral blood germline 72 multigene panel testing were enrolled for retrospective analysis. High-risk factors included: i) triple-negative breast cancer; ii) male breast cancer; iii) primary bilateral breast cancer; iv) diagnosed with breast cancer at age less than or equal to 40 years; and v) at least one first- and/or second-degree relative with BRCA-related cancer. Results: The germline pathogenic or likely pathogenic mutation rate was 29.6% (68/230) in high-risk breast cancer patients. Among them, 43 (18.7%, 43/230) were identified as harboring BRCA1/2 mutation, 30 (13.0%, 30/230) patients carried non-BRCA germline variants and 23 (10.0%, 23/230) patients were non-BRCA homologous recombination repair (HRR) gene mutation carriers. Variants were detected in 16 non-BRCA genes, including PALB2, CHEK2, ATM, TP53, RAD51D, FANCA, ATR, BARD1, BRIP1, ERCC3, HOXB13, MLH1, MRE11, RAD51C, RAD54L and PMS2. Among high-risk factors, family history showed a correlation with both BRCA (P=0.008) and non-BRCA HRR gene mutation status (P=0.023). Besides, TNBC showed a correlation with BRCA1 gene mutation status (P=0.024). In addition, 316 kinds of variants of uncertain significance (VUS) were identified among 175 (76.1%, 175/230) patients. Conclusions: Non-BRCA gene mutations are frequently identified in breast cancer patients with high risk factors. We strongly suggest that breast cancer patients with a BRCA-related family history receive comprehensive gene mutation testing, especially HRR genes, which are not only related to high risk of breast cancer, but also potentially related to poly ADP ribose polymerase inhibitor targeted therapy in China. The exact relationship of rare gene mutations to breast cancer predisposition and the pathogenicity of VUS need to be further investigated.